Indigenous bridging/foundation education: student feedback on programme successes, challenges and opportunities - Anneka Anderson; Elana Curtis; Melaney Tkatch; Belinda Loring; Sue Reddy; Kanewa Stokes; Wills Nepia; Tracey Winter; Papaarangi Reid (Springer, 2024)
Abstract Hikitia te Ora (Certificate in Health Sciences) is a 1 year Indigenous bridging foundation programme at the University of Auckland, Aotearoa New Zealand. The programme aims to increase Māori and Pacific health workforce representation. This qualitative study applied a Kaupapa Māori positioning to elucidate the strengths, challenges, and opportunities of the programme. Data were collected through two workshops and seven focus groups with a total of 67 participants who were students of Hikitia te Ora from past and present cohorts, or their family members. Using a general inductive thematic analysis, the primary themes identified were that programme successes encompassed whanaungatanga (process of establishing relationships), academic and pastoral support, programme structure and the teaching content. Challenges included social cliques and divisive social groupings, timetabling of courses and high workloads. The three areas that emerged for further development include extending Pacific content, increasing the number of students in the programme, and maintaining a programme-specific study space for students. Implementing the findings from this study into Hikitia te Ora is expected to improve educational outcomes for Māori and Pacific students and may have the potential to benefit other bridging foundation courses aiming to promote Indigenous health workforce development.